Antitrust taking on monopoly power from the gilded age to the digital age - Amy Klobuchar, with John Bessler (New York Alfred A. Knopf, a division of Penguin Random House LLC, 2021)
Monopoly - it's not just a game : the roots of America's anti-monopolist movement -- Don't trust the trusts : James J. Hill, the Gilded Age, and the labor movement -- A heartland rebellion : the grangers, a political prairie fire, and a republican authors the Sherman Act -- Teddy Roosevelt and the antitrust enforcers : the trustbusters take over the white house -- The last 100 years : a century of antitrust action (and inaction) in the courts and Congress -- We the people : why antitrust matters for our democracy and our economy -- The modern-day antitrust challenges: corporate consolidation, congressional inertia, and the conservative courts -- The path forward : the solutions to America's monopoly problem.
Includes index.
Keywords: Roosevelt, Theodore, 1858-1919.